A cumulative meta-analysis of endoscopic papillary balloon dilation versus endoscopic sphincterotomy for removal of common bile duct stones - Tringali, Alberto; Rota, Matteo; Rossi, Marta; Hassan, Cesare; Adler, Douglas G.; Mutignani, Massimiliano (Endoscopy, 2019)
Background Endoscopic papillary balloon dilation (EPBD) was introduced to overcome the risk of adverse events associated with endoscopic sphincterotomy in the removal of common bile duct (CBD) stones. We performed a meta-analysis of randomized controlled trials (RCTs) comparing efficacy and safety of EPBD vs. endoscopic sphincterotomy, focusing on stone size, balloon diameter, and balloon dilation time.Methods A multiple database search was performed, including MEDLINE, EMBASE and Cochrane Library, from their inception date until October 2017. RCTs comparing the efficacy and safety of EPBD vs. endoscopic sphincterotomy in the removal of CBD stones were included. Cumulative meta-analyses over time, and subgroup analyses according to stone size, and balloon diameter and dilation time were carried out.Results 25 RCTs met the inclusion criteria. Despite the cumulative meta-analysis showing a trend over time in favor of endoscopic sphincterotomy in studies published up to 2004, the conventional meta-analysis revealed that EPBD was equally efficacious compared with endoscopic sphincterotomy in stone removal at first attempt (odds ratio [OR] 0.95, 95 % confidence interval [CI] 0.65 – 1.38). Endoscopic sphincterotomy was superior to EPBD in terms of overall stone clearance (OR 0.65, 95 %CI 0.43 – 0.99) in studies published since 2002, but no differences emerged in studies using large ( ≥ 10 mm) balloons (OR 1.37, 95 %CI 0.72 – 2.62). No statistically significant difference in pancreatitis occurrence emerged between EPBD and endoscopic sphincterotomy (OR 1.35, 95 %CI 0.90 – 2.03). Pancreatitis was more common with EPBD than with endoscopic sphincterotomy in studies using balloons < 10 mm (OR 1.78, 95 %CI 1.07 – 2.97), whereas no difference emerged in studies using large balloons (OR 0.84, 95 %CI 0.46 – 1.53). EPBD had lower rates of bleeding and cholecystitis.Conclusions Our latest data confirm that EPBD is currently inferior to endoscopic sphincterotomy in terms of overall stone clearance. However, EPBD using large balloons (≥ 10 mm) was as effective as endoscopic sphincterotomy, both in stone clearance and the need for endoscopic mechanical lithotripsy, without carrying an increased risk of pancreatitis.